2019
DOI: 10.3390/antiox8110525
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Upregulates the Genes of the ROS Pathway and Enhances the Antioxidant Potential of Grape (Vitis vinifera L. ‘Touriga Franca’ and ’Tinto Cão’) Tissues

Abstract: Chitosan is an environmentally-friendly active molecule that has been explored for numerous agricultural uses. Its use in crop protection is well-known, however, other properties, such as bioactivity, deserve attention. Moreover, the modes of actions of chitosan remain to be elucidated. The present study assessed the levels of total phenolic compounds, the antioxidant potential, and the expression of reactive oxygen species (ROS) scavenging genes in the berries (skins and seeds), leaves, cluster stems, and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 77 publications
(113 reference statements)
2
38
0
Order By: Relevance
“…Previous studies also demonstrated that continuous chitosan application improved polyphenolic content and wine antioxidant potential when compared with the traditional fungicide treatments [7], whereas preharvest application showed no differences in these parameters [10]. Our recent study further suggested improved antioxidant potential upon chitosan application in Vitis vinifera L. [11].…”
Section: Introductionsupporting
confidence: 65%
See 4 more Smart Citations
“…Previous studies also demonstrated that continuous chitosan application improved polyphenolic content and wine antioxidant potential when compared with the traditional fungicide treatments [7], whereas preharvest application showed no differences in these parameters [10]. Our recent study further suggested improved antioxidant potential upon chitosan application in Vitis vinifera L. [11].…”
Section: Introductionsupporting
confidence: 65%
“…One report demonstrated some elicitation potential in Hypericum perforatum root cultures on xanthone biosynthesis [40]. The same amount of acetic acid solution (0.01% aqueous solution) was applied on the control grapevine in the present study to confirm the mechanism of the chitosan effect, which has been unanswered in our previous report [11]. It may be that the difference in xanthone synthesis in cultures may be due to change in culture medium properties by acetic acid and will need further investigation [40].…”
Section: Figuresupporting
confidence: 51%
See 3 more Smart Citations